Visualisation of nucleotide sequences - Rekašius, Tomas (Lietuvos matematikos rinkinys, 2023)
The paper reviews the visualisation problems of genetic sequences and of their analysis results as well as other related problems. A possible formulation of the problem based on similarity, complexity measure (distance) between DNA sequences is proposed. It is solved by making use of multidimensional scaling (MDS) of principal component analysis (PCA) methods.
Keywords: DNA sequences; complexity measure; multidimensional scaling